Effect of ukhuwwah driven social cohesiveness in governing quality innovation for sustainable development goals - Sarif, Suhaimi Mhd (Zes Rokman Resources, 2019)
Effect of ukhuwwah driven social cohesiveness in governing quality innovation for sustainable development goals ukhuwwah enables cohesiveness among innovation workers in ensuring the governance of quality innovation. While rules and procedures are essential, ukhuwwah reinforces qualitatively with soul, spirituality and consciousness. Social equity theory deliberates the weight of the rewards. Thus, this study aims to explore the effect of ukhuwwah in governing quality innovation for sustainable development goals, specifically in Malaysia. This study uses personal interview with 10 innovation workers in Malaysia. The feedback from the informants argued that ukhuwwah combines cohesiveness and weight of rewards to sustain development goals with more governance and innovation framework. Future studies should use case study method to deliberate the proposition in more integrated, comprehensive and rigorous.